Kamao mga kuwento ng protesta, 1970-1986 - Salanga, Alfrredo Navarro; Cultural Center of the Philippines (Manila Center for Literature, Cultural Center of the Philippines, 1987)
An anthology of articles and stories published during the period from just prior to the beginning of Fernand Marcos' presidency through the period immediately after its end.
Cover has subtitle: Panitikan ng protesta 1970-1986.
Fi-9042g donated by Dr. Ma. Teresa Sicat.
Keywords: Short stories, Philippine; Political fiction; Protest literature, Tagalog; Philippines -- Politics and government -- 1973-1986 -- Fiction